Influence of postnatal prolactin modulation on the development and maturation of ventral prostate in young rats - Camargo, Ana C. L. [UNESP]; Constantino, Flavia B. [UNESP]; Santos, Sergio A. A. [UNESP]; Colombelli, Ketlin T. [UNESP]; Dal-Pai-Silva, Maeli [UNESP]; Felisbino, Sergio L.; Justulin, Luis A. [UNESP] (Csiro Publishing, 2018)
Besides androgenic dependence, other hormones also influence the prostate biology. Prolactin has been described as an important hormone associated with maintenance of prostatic morphophysiology; however, there is a lack of information on the involvement of prolactin during prostate development and growth. This study aimed to evaluate whether perinatal prolactin modulation interferes with rat ventral prostate (VP) development and maturation. Therefore, prolactin or bromocriptine (an inhibitor of prolactin release from the pituitary) were administered to Sprague Dawley rats from postnatal Day (PND) 12 to PND 21 or 35. Animals were then killed and serum hormonal quantification, VP morphological-stereological and immunohistochemical analyses and western blotting reactions were employed. Our results demonstrate that prolactin blockage increased serum testosterone on PND 21, which reflected an increase in anogenital distance. Although prolactin modulation did not interfere with VP weight, it modified VP morphology by dilating the acinar lumen and reducing epithelial cell height. Prolactin activated the signal transducer and activator of transcription (STAT) downstream pathway, increased androgen receptor expression and epithelial proliferation. In addition, prolactin and bromocriptine also increased expression of cytokeratin 18, a marker of luminal-differentiated cells. In conclusion, the VP responds to prolactin modulation through a mechanism of increasing the epithelial proliferative response and dynamics of cell differentiation, especially in animals treated for a more prolonged period.
Keywords: bromocriptine